Synthesis and characterization of Ethiopian kaolin for the removal of basic yellow (BY 28) dye from aqueous solution as a potential adsorbent. Issue 9 (September 2020) - Aragaw, Tadele Assefa; Angerasa, Fikiru Temesgen
Abstract: In the present research, the kaolin adsorbents (beneficiated, raw powder, and calcined) were prepared from Ethiopian natural kaolin through mechanical, wet, and thermal processes. The geochemical and surface properties of kaolin adsorbent were characterized using FTIR, SEM/EDS, XRD, and XRF. In the batch experiment, basic operation parameters (initial dye concentrations, pH, temperature, contact time, and adsorbent dosage) were examined. Percentage removal efficiency basic yellow 28 (BY28) dye were recorded as 94.79%, 92.08%, and 87.08% onto beneficiated, raw, and calcined kaolin absorbents, respectively at an initial dye concentration of 20 mg/L, solution pH of 9, the temperature of 30 °C °C, and contact time of 60 min and adsorbent dosage of 1g/100L. The molar ratio of SiO2 /Al2 O3 was recorded as 2.911 Percent mass composition of Ethiopian kaolin which is higher than the expected pure kaolinite standard which allows us to classify the kaolin clay as a siliceous one. The calculated values of Δ G 0 for beneficiated adsorbent are -1.243, 1.576, and 4.396 kJ/mol at 303.15, 323.15, and 343.15 K, respectively for 20 mg/L of dye concentration and solution pH of 9, suggests that the thermodynamic behavior at lowest temperature is more feasible and spontaneous as compared with the higher temperature one. A similar fashion was calculated for raw and calcined adsorbents. The negative values of ΔH o and ΔS° suggest that the adsorption phenomenon is exothermic and the adsorbate molecules are organized on the solid phase in a more disordered fashion than the liquid phase. The pseudo-first-order and pseudo-second-order models have been used to describe the kinetics in the adsorption processes. The Pseudo-second-order model has been fitted for the BY 28 dye adsorption in the studied concentration range. The adsorption of BY 28 dye for raw and calcined adsorbents follows the Langmuir isotherm and the Freundlich isotherm fitted for the beneficiated adsorbent. The amount of BY28 dye taken up by beneficiated, raw, and calcined kaolin adsorbents was found as 1.896, 1.842, and 1.742 mg/g, respectively at a contact time of 1.0 h, the adsorbent dosage of 1.0 g, initial dye concentration = 20 mg/L and solution pH = 9 at 30 °C. The results found that these raw and prepared local kaolin adsorbents have a capacity as low-cost alternatives for the removal of dyes in industrial wastewater. Abstract : Materials science, Chemical engineering, Dye wastewater, Kaolin, Adsorption, BY 28 dye, Adsorbent synthesis, Characterization.